Performance Analysis of MIMO STBC System in Flat Fading and Frequency Selective Fading Channels - Samosir, Pebri Yeni; Pramaita, Nyoman; Hartawan, I Gst A. Komang Diafari Djuni; Wirastuti, Ni Made Ary Esta Dewi (Journal of Electrical, Electronics and Informatics; Vol 3 No 1 (2019): JEEI (February 2019), 2019)
Multiple Input Multiple Output (MIMO) technology is a technique that can be used to overcome multipath fading. The multipath fading is caused by signals coming from several paths that experience different attenuations, delays and phases. In a multipath condition, an impulse that sent by the transmitter, will be received by the recipient not as an impulse but as a pulse with a spread width that called delay spread. Delay spread can cause intersymbol interference (ISI) and bit translation errors from the information received. To determine the effect of delay spread on the MIMO system, then MIMO system performance research was performed on flat fading and frequency selective fading channels using the Space Time Block Code (STBC) coding technique. This research was conducted using MatLab 2018a software. The simulation results show that the MIMO STBC system performance on flat fading channels is better than the MIMO STBC system performance on the frequency selective fading channel. This result is analyzed based on the value of BER vs. Eb/No and eye diagram.